Food service attributes on customer satisfaction: a study on cafeteria in UiTM Terengganu, Dungun Campus / Muhammad Hazim Mohd Fauzi and Muhamad Izham Radzali - Mohd Fauzi, Muhammad Hazim; Radzali, Muhamad Izham (2021)
Nature of food service attributes always come from service quality, ambience, price and food quality. The purpose of this study is to identify the effect of food service attributes towards customer satisfaction in UiTM Dungun Cafeteria. Which is the food service attributes are service quality, ambience, price and food quality. A sample of 195 students who had dine in one of the cafeteria in UiTM Dungun are surveyed in order to examine the food service attributes and to test the significant relationship between food service attributes with customer satisfaction. Pearson correlation coefficients were utilized to analyse the data. Where as means scores and frequencies were computed. The result of the study indicated that there is a significant relationship between food service attributes (service quality, ambience, price and food quality) with customer satisfaction in UiTM Dungun cafeteria.